PEMBENTUKAN JIWA KEWIRAUSAHAN MAHASISWA PROGRAM STUDI BAHASA JERMAN - Jolanda Tomasouw; Juliaans E R Marantika; Henderika Serpara (German für Gesellschaft (J-Gefüge), 2022)
The purpose of the service is to grow the entrepreneurial spirit and values ​​of students for business independence from the aspects of entrepreneurial spirit, entrepreneurial behavior, and business independence. The development of technology, especially information technology, has fostered an entrepreneurial spirit and is very important to be grown in one's soul. Among students, the interest in working in entrepreneurship is minimal, so they still think college is only for being an employee or employee. In addition, several factors cause students to be less interested in entrepreneurship, namely, there is no capital to start a business, or they are never equipped with knowledge about entrepreneurship. The mindset of students needs to be addressed to understand better how significant the role of entrepreneurship is in everyday life. This part of education, especially in higher education, is essential to foster student interest in entrepreneurship so that limited employment opportunities are no longer a big problem because students can run their businesses. The targets in service activities are students of the German Language Study Program in semester 3 of the 2022/2023 academic year. The data were collected using interview techniques for small entrepreneurs and questionnaires for students. To further improve students' abilities, the government has provided a forum for students who want to learn